Food Webs and Niche Space. (MPB-11), Volume 11 - Cohen, Joel E.; Stephens, David W. (Princeton University Press, 2020)
What is the minimum dimension of a niche space necessary to represent the overlaps among observed niches? This book presents a new technique for obtaining a partial answer to this elementary question about niche space. The author bases his technique on a relation between the combinatorial structure of food webs and the mathematical theory of interval graphs. Professor Cohen collects more than thirty food webs from the ecological literature and analyzes their statistical and combinatorial properties in detail. As a result, he is able to generalize: within habitats of a certain limited physical and temporal heterogeneity, the overlaps among niches, along their trophic (feeding) dimensions, can be represented in a one-dimensional niche space far more often than would be expected by chance alone and perhaps always. This compatibility has not previously been noticed. It indicates that real food webs fall in a small subset of the mathematically possible food webs. Professor Cohen discusses other apparently new features of real food webs, including the constant ratio of the number of kinds of prey to the number of kinds of predators in food webs that describe a community. In conclusion he discusses possible extensions and limitations of his results and suggests directions for future research
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Apr 2020)
Keywords: Conus; Desmognathus; Hawaii; Lake Nyasa; Monte Carlo simulation; algorithm; Accipiter; aspen forest; column average; column variance; composite community; creek; eating relation; feeding relation; gastropods; independence of niche dimensions; inequalities; intersection graph; marine bench; niche overlap graph; overlap; predator; pseudo-random food web; qualitative stability; resource partitioning; salamanders; sampling; sink food web; temperature; uniform distribution; variance test; SCIENCE / Life Sciences / Ecology; Food chains (Ecology); Niche (Ecology)